A educação com inspiração cidadã como elemento redutor da morosidade do Poder Judiciário - Braga, Sérgio Pereira (2016)
This study aims to identify alternatives that may contribute to reduce the slowness in the Judiciary. It is assumed that if everyone has access to quality and citizen education, several issues, that are now growing in volume and increasing the congestion in the Judiciary, could be settled in systems other than judicial. Therefore, this thesis begins with the history of citizenship, since the outbreak of its first traces in the Greek polis to the present day, including the achievements and setbacks in this historic route. Then, it presents the Brazilian people formation, from the Portuguese colonization, emphasizing characteristic traits of our society, especially flexible or relative ethics; the "Brazilian way", and the principle of duality. Later, the causes of slow pace of justice and their overlaps will be described, as well as the effects of the delay according to the fundamental guarantee of reasonable duration of the process and the challenges to its effectiveness. Finally, from the analysis of social and familiar relationship disintegration, effects of postmodernity, the citizen education is presented as a remedy for the proceedings backlog. People who are well-educated in schools and as citizens may help to reduce the complex issue of slowness in the Judiciary. Besides, they may claim their rights and fulfill their duties. In this particular aspect, the key role of higher education institutions revives, especially the bachelor's degree programs in Law, which can and should be the leaders and propagators of such civic education. The research is conducted by the inductive method and the research technique applied was bibliographic